Cytokine induction by lipopolysaccharide (LPS) corresponds to lethal toxicity and is inhibited by nontoxic Rhodobacter capsulatus LPS. - Loppnow, H (1990)
Many pathological effects of gram-negative bacteria are produced by their cell wall-derived lipopolysaccharides (LPSs). Differing pathogenicity of gram-negative LPSs, however, may depend on their capacities to induce cytokines. Thus, we studied the lethal toxicity of four nonenterobacterial LPSs and compared it with their capacity to induce mononuclear cell (MNC)-derived interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor (TNF). Unstimulated MNC did not release these cytokines. LPS from the phototrophic strain Rhodobacter capsulatus 37b4 elaborated little toxicity in galactosamine-treated mice (10 micrograms of LPS per mouse was the 100% lethal dose [LD100]) and induced IL-1 and IL-6 release only at high concentrations (10 to 50 micrograms of LPS per ml). R. capsulatus LPS failed to induce TNF activity even at the highest concentration tested (100 micrograms of LPS per ml). In contrast, LPS derived from Pseudomonas diminuta NCTC 8545 or the nodulating species Bradyrhizobium lupini DSM 30140 and Rhizobium meliloti 10406 expressed lethal toxicity (LD100, 1,000, 100, and 10 ng per mouse, respectively) and induced IL-1 or IL-6 (10 to 100, 10, and 1 ng of LPS per ml, respectively) at concentrations 1,000- to 10,000-fold lower than effective levels of R. capsulatus LPS. LPSs from P. diminuta, B. lupini, and R. meliloti also stimulated TNF production and release. MNC accumulated cell-associated IL-1 activities under circumstances in which released activity was readily detected. The cells contained only scant IL-6 activity, indicating release of this mediator rather than intracellular accumulation. Antisera to the respective cytokines inactivated biological activities of the samples selectively. The R. capsulatus LPS inhibited cytokine induction by LPS from P. diminuta, B. lupini, and R. meliloti in coincubation experiments. These results show that the in vivo lethality of the LPSs tested correlates with the induction of monocyte-derived cytokines in vitro. The results of this study suggest that the different lethality of various LPSs from gram-negative bacteria may be due to the differential ability of these LPSs to induce cytokine production.